Variable-temperature tensile testing device for functional film

By designing a temperature-changing tensile testing device for functional films, the problem of insufficient testing capabilities of existing equipment under temperature-changing conditions is solved, and accurate testing is achieved in the range of 0 to 200℃, which improves the accuracy and reliability of the test results. Supports the development of high-performance film materials.

CN119321960APending Publication Date: 2025-01-17TIANJIN UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411769155.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing film tensile testing equipment has limited testing capabilities under variable temperature conditions in simulated actual working environments, and it is impossible to fully evaluate the performance changes of materials at different temperatures. In addition, there are sample processing and thickness control challenges in micro-tension testing, which limits the test results. accuracy and reliability.

Method used

A variable temperature tensile testing device is designed, including a shell, support platform, force sensor, power guide rail and fixture. Combined with electric heating elements and temperature controller, it can accurately control within the temperature range of 0 to 200℃ to achieve lossless nanometers. Film sample treatment and tensile testing.

Benefits of technology

Improves the accuracy and reliability of test results, covers the practical application environment of most materials, and provides critical data to support the development and optimization of high-performance materials, especially performance evaluation at extreme temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119321960A_ABST
    Figure CN119321960A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of film testing, in particular to a variable-temperature tensile testing device for a functional film. According to the specific technical scheme, the variable-temperature tensile testing device for the functional film comprises a shell, a supporting platform is arranged in the shell, a force sensor is arranged on the supporting platform, a left clamp is connected to a sensing shaft of the force sensor, a power guide rail is arranged in the shell, and a right clamp is arranged on the power guide rail. A right clamp corresponding to the left clamp is arranged on the power guide rail, and the bottom of the left clamp and the bottom of the right clamp are horizontally arranged. The testing device disclosed by the invention can test the performance of the nano-film under different temperature conditions, and provides valuable information for stress-strain curves of various functional films under different temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of film testing, and in particular to a variable temperature stretching testing device for functional films. Background Art

[0002] Functional thin film materials play a vital role in modern science and industry due to their unique physical, chemical and biological functions. These materials are usually at the nanometer level and can significantly improve the performance of the base material. With the rapid development of science and technology, the market demand for high-performance thin film materials is growing, especially in the fields of flexible electronics, efficient energy storage and biocompatible medical devices.

[0003] Functional films are widely used in the electronics field for photodetectors, integrated circuits, display devices, etc., which improve the integration and flexibility of electronic devices. In the energy field, functional film materials are used in new energy batteries and photovoltaic industries, and are expected to achieve innovative applications in smart windows and solar panels. Functional films also play an important role in the biomedical and medical fields, showing great application potential in health protection, safe energy storage, and battlefield first aid. The application of functional films in green and energy-saving buildings helps to improve the energy efficiency and environmental performance of buildings. In addition, the demand for functional films in the aerospace field is also increasing.

[0004] Modern film stretching testing equipment is not only suitable for tensile properties testing of plastic films, composite films and metal films, but also can perform a variety of mechanical properties tests such as peeling, deformation, tearing, etc. Some equipment can perform in-situ observations under a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and monitor the microstructural changes of the material during the stretching process in real time. However, existing technologies have limitations in simulating the stretching process in an actual working environment, especially in the testing capabilities under variable temperature conditions. For example, existing nanoindentation tests are limited by experimental conditions and often cannot fully evaluate the performance changes of materials at different temperatures. In addition, micro-tensile testing has challenges in sample processing and film thickness control, which limits the accuracy and reliability of test results. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a variable temperature stretching test device for functional films, which can test the performance of nanofilms under different temperature conditions and provide valuable information for the stress-strain curves of various functional films at different temperatures.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] The present invention discloses a variable temperature stretching testing device for a functional film, comprising a shell, a supporting platform arranged inside the shell, a force sensor arranged on the supporting platform, a left clamp connected to the sensing axis of the force sensor, a power guide rail arranged inside the shell, a right clamp corresponding to the left clamp arranged on the power guide rail, and the bottoms of the left clamp and the right clamp are arranged horizontally.

[0008] Preferably, a support frame is provided on the support platform, and the force sensor is provided on the support frame.

[0009] Preferably, a fixed axis piece is provided on the sensing axis of the force sensor.

[0010] Preferably, a water tank is provided below the left clamp and the right clamp, an electric heating element and a temperature controller connected thereto are provided in the water tank, and a temperature sensor is provided in the water tank.

[0011] Preferably, the power guide rail includes a screw rod and a motor connected to the screw rod, a nut is provided on the screw rod, the right clamp is fixed on the nut, and a displacement collector is provided on the screw rod.

[0012] Correspondingly, a variable temperature tensile test method for a functional film is provided. After a film is prepared on a glass sheet, it is placed in a water tank, and the film is allowed to fall off and float on the water surface. The film is located under left and right clamps, the water surface is raised, and the left and right clamps adhere the film, and then a tensile test is performed.

[0013] Preferably, the film is subjected to a tensile test at a temperature between 0 and 200°C.

[0014] Preferably, the film has a thickness of 10 nm to 10 μm, and includes one or more blended films of pure component films, conjugated polymer films, elastomer films, inorganic semiconductor films, oxide films, organic films, and carbon material nanofilms.

[0015] Preferably, the pure component film is a metal film; the organic film is at least one of polyolefin, polyamide, polystyrene, and polythiophene; the conjugated polymer material used in the conjugated polymer film is PBDB-T, PM6, PDFD-T, PffBT4T-2OD, P3AT, PTAA, FTAZ, PNDITF4T, BBL, PCDTBT, PBDTTPD, N2200, PDPP3T, PTB7-Th, PTB7, PY-IT, PPDT2FBT, PTPD3T, PDPPTPT, PTQ1, PFBCPZ, TIPS-TPD, PTVT-T, PM7 , PDTP-DPP, PBDTTPD-HT, asy-ranPBTBDT, PBnDT-FTAZ, J71, PTzBi-Si, D18, D18-Cl, PDPPSDTPS, CC1C10-PPV, PBQX-TCI, P4T2F-HD, PCPDTBT, Si-PCPDTBT, PBT(TH), PBD(EDOT), PBD(TH), PDCBT, PDTPBT, PDCBT-CI, PTQ10, PNDI-5DD, PNDI-POD, IDTBT, PDMS, PS, SEBS, any one or more.

[0016] The present invention has the following beneficial effects:

[0017] The present invention introduces non-destructive non-composite nanofilm sample processing technology and integrates an advanced temperature control module to achieve accurate tensile testing of nanofilm materials under different temperature conditions. The temperature sensor has the characteristics of high precision and fast response, and can accurately control the test temperature, providing key data support for the development and optimization of high-performance materials.

[0018] Compared with the prior art, the present invention has significant advantages in multiple key performance indicators. First, the sample processing technology reduces damage during sample preparation and improves the accuracy and reliability of the test results. Secondly, the test device can provide a wide temperature test range, which can extend from low temperatures close to 0°C to high temperatures of 200°C, covering the actual application environment of most materials. Finally, the test device can achieve more precise temperature control, which is crucial for evaluating the performance of materials under extreme temperatures. These advantages make the present invention have important application value in the development and optimization of high-performance thin film materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the structure of the present invention;

[0020] Figure 2 Schematic diagram of displacement and time, stress and time, and stress and displacement during the detection process.

[0022] Figure 3 It is a schematic diagram of stretching control;

[0023] Figure 4 Schematic diagram of the cyclic stretching setup;

[0024] Figure 5 This is the stress-strain curve of N2200 film under fixed strain cyclic stretching at room temperature;

[0025] Figure 6 is the stress-strain curve of IDTBT film at different temperatures;

[0026] Figure 7 is the stress-strain curve of P3PT film under cyclic stretching at room temperature;

[0027] Figure 8 is the stress-strain curve of the gold film stretched at room temperature;

[0028] Fig. 9 The stress-strain curves of PTzBI-Si, PM6, PTVT-T, and PTQ10 films stretched at room temperature;

[0029] Fig.10 The stress-strain curves of PTQ10 and N2200 films with different ratios stretched at room temperature;

[0030] Fig.11 The stress-strain curves of PM6: PY-IT: N2200 blend films with different molecular weights stretched at room temperature;

[0031] Fig.12 The stress-strain curves of elastomer blend films with different weight fractions;

[0032] In the figure: housing 1, support platform 2, support frame 3, force sensor 4, fixed axis piece 5, water tank 6, left clamp 7, power guide rail 8, button 9, right clamp 10, water outlet 11, water pump 12. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0035] refer to Figure 1 The present invention discloses a variable temperature tensile testing device for functional films, comprising a housing 1, a support platform 2 is arranged in the housing 1, the support platform provides a certain height, a force sensor 4 is arranged on the support platform 2, a left clamp 7 is connected to the sensing axis of the force sensor 4, a power rail 8 is arranged in the housing 1, a right clamp 10 corresponding to the left clamp 7 is arranged on the power rail 8, and the bottoms (i.e., the lower surfaces) of the left clamp 7 and the right clamp 10 are arranged horizontally. The left clamp 7 and the right clamp 10 are used to fix the film sample. After the film sample is fixed, the tensile state of the film sample can be adjusted by controlling the power rail 8, and the force sensor 4 can detect the tensile stress of the film sample, and then determine its tensile strain.

[0036] Furthermore, a support frame 3 is provided on the support platform 2, and the force sensor 4 is provided on the support frame 3, that is, the support frame is used to fix the force sensor.

[0037] Furthermore, a fixed axis piece 5 is provided on the sensing axis of the force sensor 4 for stabilizing the sensing axis of the force sensor, and the fixed axis piece can adjust the size of the center hole.

[0038] Furthermore, a water tank 6 is provided below the left clamp 7 and the right clamp 10. The water tank is used to provide a horizontal liquid surface. An electric heating element and a temperature controller connected thereto are provided in the water tank 6. A temperature sensor is provided in the water tank 6 to measure the temperature of the liquid in the water tank. A water pump 12 is connected to the water tank to control the height of the liquid level in the water tank. A water outlet 11 is provided on the side wall of the water tank. Since the temperature field of the film sample is higher than the normal room temperature environment, it only needs to be heated up. The electric heating element is used for heating up. The temperature controller is connected to the temperature sensor to collect the current temperature value. If the current temperature value reaches the set temperature value, the electric heating element is controlled by the temperature controller to stop heating up. In this way, the temperature can be controlled within the set temperature range through the water tank 6.

[0039] Furthermore, the power guide rail 8 includes a screw and a motor connected to the screw, a nut is provided on the screw, the right clamp 10 is fixed on the nut, and a displacement collector is provided on the screw, and the displacement collector obtains the displacement by collecting the number of rotations of the screw and multiplying it by the pitch of the screw. When in use, by controlling the operating parameters of the motor, such as speed, torque, etc., the speed at which the left clamp 7 and the right clamp 10 move toward or away from each other can be controlled, thereby achieving control of the stretching rate of the film sample. Among them, the screw can be set to two to ensure the stability of the drive.

[0040] The present invention also discloses a test method based on a variable temperature stretch test device for functional films, wherein a film is prepared on a glass sheet and placed in a water tank 6, the film is allowed to fall off and float on the water surface, the film is located below the left and right clamps 10, the water surface is raised, the left and right clamps 10 adhere the film, and then a stretch test is performed. The film sample of the present invention includes a substrate and a functional film deposited on the substrate, and the deposition method of the functional film includes but is not limited to spin coating, drop coating, scraper coating, and vacuum evaporation.

[0041] The film is subjected to a tensile test between 0 and 200°C, that is, the test temperature is controlled during the test, and the temperature is varied between 0 and 200°C (preferably 10 to 200°C, and more preferably 20 to 200°C) through a heating-temperature measurement-feedback loop to obtain film stress-strain curves under different temperature fields.

[0042] Furthermore, the thickness of the film is 10nm to 10μm, including one or more blended films of pure component films, conjugated polymer films, elastomer films, inorganic semiconductor films (such as AlGaN, Si, etc.), oxide films (such as TiO2, ZnO, etc.), organic films, and carbon material nanofilms (such as graphene, carbon nanotubes, etc.).

[0043] The pure component film is a metal film, such as copper, silver, etc.; the organic film is at least one of polyolefin, polyamide, polystyrene, and polythiophene; the conjugated polymer material used in the conjugated polymer film is PBDB-T, PM6, PDFD-T, PffBT4T-2OD, P3AT, PTAA, FTAZ, PNDITF4T, BBL, PCDTBT, PBDTTPD, N2200, PDPP3T, PTB7-Th, PTB7, PY-IT, PPDT2FBT, PTPD3T, PDPPTPT, PTQ1, PFBCPZ, TIPS-TPD, PTVT-T , PM7, PDTP-DPP, PBDTTPD-HT, asy-ranPBTBDT, PBnDT-FTAZ, J71, PTzBi-Si, D18, D18-Cl, PDPPSDTPS, CC1C10-PPV, PBQX-TCI, P4T2F-HD, PCPDTBT, Si-PCPDTBT, PBTTH, PBDEDOT, PBDTH, PDCBT, PDTPBT, PDCBT-CI, PTQ10, PNDI-5DD, PNDI-POD, IDTBT, PDMS, PS, SEBS, any one or more. The specific molecular structure is as follows:

[0044]

[0045]

[0046]

[0047] When the testing device disclosed in the present invention is used to perform a tensile test, some important information can be recorded based on the set sensors and the control of the power rail, such as Figure 2 , 3 , 4. Displacement and time, stress and time, and stress and displacement can be recorded during the measurement process.

[0048] The present invention will be further described below in conjunction with specific embodiments.

[0049] Example 1

[0050] The glass sheet was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass sheet was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, and the modified glass sheet was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; a certain mass of N2200 was weighed, chloroform was added, and a chloroform solution with a concentration of 15mg / mL was prepared, and it was placed on a hot plate at 40℃ and stirred overnight to dissolve into a uniform solution. The dissolved N2200 solution was spin-coated on the surface, and after the film was formed, it was placed on a hot plate at 100℃ for annealing for 10min; the glass sheet was slowly placed in water, and the film fell off the glass sheet and floated on the water surface. The film was placed under the fixture, and the water surface was lifted. When the fixture contacts the film, the film will adhere. Set the stretching rate to 3mm / min, the stretching strain to 15%, and the number of stretches to 10. Set the tension to zero and start stretching. Figure 5 This is the stress-strain curve of N2200 film under fixed strain cyclic stretching at room temperature.

[0051] Example 2

[0052] The glass slide was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass slide was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, and the modified glass slide was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; a certain mass of IDTBT was weighed, chloroform was added, and a chloroform solution with a concentration of 15mg / mL was prepared, and it was placed on a hot plate at 40℃ and stirred overnight to dissolve into a uniform solution. The dissolved IDTBT solution was spin-coated on the surface, and after the film was formed, it was placed on a hot plate at 100℃ for annealing for 10min; the glass slide was slowly placed in water, and the film fell off the glass slide and floated on the water surface. The film was placed under the fixture, and the water surface was lifted. When the fixture contacts the film, the film will adhere. Set the stretching rate to 3mm / min and the tensile strain to break. Set the water temperature to 30℃, 40℃, 50℃, 60℃, 70℃, 80℃ and 90℃. Set the tension to zero at each temperature and start stretching. Figure 6 Stress-strain curves of IDTBT films at different temperatures.

[0053] Example 3

[0054] The glass slide was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass slide was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, and the modified glass slide was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; a certain mass of P3PT was weighed, chloroform was added, and a chloroform solution with a concentration of 15mg / mL was prepared, and it was placed on a hot plate at 40℃ and stirred overnight to dissolve into a uniform solution. The dissolved P3PT solution was spin-coated on the surface, and after the film was formed, it was placed on a hot plate at 100℃ for annealing for 10min; the glass slide was slowly placed in water, and the film fell off the glass slide and floated on the water surface. The film was placed under the fixture, and the water surface was lifted. When the fixture contacts the film, the film will adhere. The stretching rate was set to 10mm / min. Set the tensile strain to 0%, 5%, 10%, 20%, 30%, 40%, 50%, 80% and 100% respectively. Set the tension to zero and start stretching. Figure 7 This is the stress-strain curve of P3PT film under cyclic stretching at room temperature.

[0055] Example 4

[0056] A 2 mm thick copper (Cu) film was deposited on a SiO2 / Si substrate by electron beam evaporation. The copper film served as a sacrificial layer for the subsequent water-assisted stripping process and for releasing the gold (Au) sample to the surface of the etching solution by copper wet etching. The Au / Cu layer can be easily stripped from the SiO2 / Si substrate due to the weak adhesion between Cu and silicon dioxide (SiO2). This process was performed at the water interface, allowing the Au / Cu layer to float on the water surface. An initial crack was created by introducing a tape between Cu and SiO2. Subsequently, the Au / Cu layer was transferred from the water surface to the surface of the etching solution by scooping. A water-diluted ferric chloride (FeCl3) solution was used as an oxidizing etchant, which effectively removed the Cu substrate without producing gaseous byproducts or precipitates. After the Cu etching was completed, the ultrathin Au film sample floated on the surface of the etching solution. The sample on the etching solution was scooped up and transferred to the water surface. The film was positioned under the fixture and the fixture was attached to the film by lifting the water surface so that the fixture contacted the film. The stretching rate was set to 0.5 mm / min, and the tension was adjusted to zero before stretching began until the film broke. Figure 8 This is the stress-strain curve of the gold film stretched at room temperature.

[0057] Example 5

[0058] The glass sheet was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass sheet was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, and the modified glass sheet was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; a certain mass of PTzBI-Si, PM6, PTVT-T, and PTQ10 was weighed, chlorobenzene was added, and a chlorobenzene solution with a concentration of 14mg / mL was prepared, and it was placed on a hot plate at 80℃ and stirred overnight to dissolve into a uniform solution. The dissolved PTzBI-Si, PM6, PTVT-T, and PTQ10 solutions were spin-coated on the surface, and after the film was formed, it was placed on a hot plate at 100℃ for annealing for 10min; the glass sheet was slowly placed in water, and the film fell off the glass sheet and floated on the water surface. Place the film under the clamp, raise the water surface, and when the clamp contacts the film, it will adhere to it. Set the stretching rate to 3mm / min, adjust the tension to zero, and start stretching until the film breaks. Fig. 9 These are the stress-strain curves of PTzBI-Si, PM6, PTVT-T, and PTQ10 films stretched at room temperature.

[0059] Example 6

[0060] The glass slide was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass slide was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, and the modified glass slide was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; PTQ10 and N2200 were weighed in a certain mass ratio of 10:1, 2:1, 1:1, 1:2, and 1:10, and chlorobenzene was added to prepare a chlorobenzene solution with a concentration of 14mg / mL, placed on a hot plate at 80℃ and stirred overnight to dissolve into a uniform solution. The dissolved solution was spin-coated on the surface, and after the film was formed, it was placed on a hot plate at 100℃ for annealing for 10min; the glass slide was slowly placed in water, and the film fell off the glass slide and floated on the water surface. Place the film under the clamp, raise the water surface, and when the clamp contacts the film, it will adhere to it. Set the stretching rate to 3mm / min, adjust the tension to zero, and start stretching until the film breaks. Fig.10 The stress-strain curves of PTQ10 and N2200 films with different ratios stretched at room temperature.

[0061] Example 7

[0062] The glass slide was soaked and cleaned in isopropanol, distilled water, acetone and isopropanol in sequence; the soaked glass slide was modified by ultraviolet ozone for 15 minutes; a 30% mass fraction of sodium polystyrene sulfonate (PSS) (weight average molecular weight is about ~200000) aqueous solution was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, the modified glass slide was covered with the PSS diluted solution, and then annealed to obtain a PSS-modified glass substrate; a certain mass of PM6, PY-IT and six batches of N2200 with different molecular weights (53k, 84k, 123k, 180k, 217k, 251k) were weighed at a mass ratio of 1:1:0.2, chloroform was added to prepare a chloroform solution with a concentration of 14 mg / mL, and it was placed on a hot stage at 40°C and stirred overnight to dissolve into a uniform solution. Spin the dissolved solution on the surface, and place it on a hot plate at 100°C for annealing for 10 minutes after the film is formed; slowly put the glass sheet into the water, and the film will fall off the glass sheet and float on the water surface. Place the film under the fixture, lift the water surface, and when the fixture contacts the film, it will adhere to the film. Set the stretching rate to 3mm / min, adjust the tension to zero, and start stretching until the film breaks and then stop. Fig.11 The stress-strain curves of PM6: PY-IT: N2200 blend films with different molecular weights stretched at room temperature.

[0063] Example 8

[0064] The glass slide was soaked and cleaned in isopropanol, distilled water, acetone, and isopropanol in turn; the soaked glass slide was modified by ultraviolet ozone for 15 minutes; a 30% sodium polystyrene sulfonate (PSS) aqueous solution (weight average molecular weight is about ~200000) was diluted, 25mL of PSS concentrated solution was mixed with 75mL of deionized water to form a PSS diluted solution, the modified glass slide was covered with the PSS diluted solution, and then annealed to obtain a glass substrate modified by PSS; a certain mass of PM6, PYFT-o and elastomer were weighed in a certain proportion, and the weight ratio of donor PM6 to acceptor (PYFT-o and elastomer) was kept constant (1:1). The weight ratio of the conjugated polymer: elastomer blend system was 1:0, 1:0.05, 1:0.1, 1:0.2, 1:0.5, 1:5, 1:10 and 0:1. Add chloroform to make a chloroform solution with a concentration of 14 mg / mL, place it on a hot plate at 40°C and stir overnight to dissolve it into a uniform solution. Spin-coat the dissolved P3PT solution on the surface, and place it on a hot plate at 100°C for annealing for 10 minutes after the film is formed; slowly put the glass sheet into the water, and the film will fall off the glass sheet and float on the water surface. Place the film under the fixture, lift the water surface, and when the fixture contacts the film, it will adhere to the film. Set the stretching rate to 3 mm / min, adjust the tension to zero, and start stretching until the film breaks and then stop. Fig.12 Shown are the stress-strain curves of elastomer blend films with different weight fractions.

[0065] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0066] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A variable temperature tensile testing device for a functional film, comprising a housing (1), characterized in that: A support platform (2) is arranged in the shell (1), a force sensor (4) is arranged on the support platform (2), a left clamp (7) is connected to the sensing axis of the force sensor (4), a power guide rail (8) is arranged in the shell (1), a right clamp (10) corresponding to the left clamp (7) is arranged on the power guide rail (8), and the bottoms of the left clamp (7) and the right clamp (10) are arranged horizontally.

2. The variable temperature stretching test device for functional films according to claim 1, characterized in that: A support frame (3) is arranged on the support platform (2), and the force sensor (4) is arranged on the support frame (3).

3. The variable temperature stretching test device for functional films according to claim 1, characterized in that: A fixed axis piece (5) is arranged on the sensing axis of the force sensor (4).

4. The variable temperature stretching test device for functional films according to claim 1, characterized in that: A water tank (6) is arranged below the left clamp (7) and the right clamp (10), an electric heating element and a temperature controller connected thereto are arranged in the water tank (6), and a temperature sensor is arranged in the water tank (6).

5. The variable temperature stretching test device for functional films according to claim 1, characterized in that: The power guide rail (8) comprises a screw rod and a motor connected to the screw rod, a nut is arranged on the screw rod, the right clamp (10) is fixed on the nut, and a displacement collector is arranged on the screw rod.

6. A testing method based on the variable temperature stretching testing device for functional films according to any one of claims 1 to 5, characterized in that: After the film is prepared on the glass sheet, it is placed in a water tank (6) to make the film fall off and float on the water surface. The film is located below the left and right clamps (10). The water surface is raised, and the left and right clamps (10) adhere the film, and then a tensile test is performed.

7. The testing method according to claim 6, characterized in that: The film is subjected to a tensile test at a temperature between 0 and 200°C.

8. The testing method according to claim 6, characterized in that: The film has a thickness of 10 nm to 10 μm, and includes one or more blended films of pure component films, conjugated polymer films, elastomer films, inorganic semiconductor films, oxide films, organic films, and carbon material nanofilms.

9. The testing method according to claim 8, characterized in that: The pure component film is a metal film; the organic film is at least one of polyolefin, polyamide, polystyrene, and polythiophene; the conjugated polymer material used in the conjugated polymer film is PBDB-T, PM6, PDFD-T, PffBT4T-2OD, P3AT, PTAA, FTAZ, PNDITF4T, BBL, PCDTBT, PBDTTPD, N2200, PDPP3T, PTB7-Th, PTB7, PY-IT, PPDT2FBT, PTPD3T, PDPPTPT, PTQ1, PFBCPZ, TIPS-TPD, PTVT-T, PM7, P Any one or more of DTP-DPP, PBDTTPD-HT, asy-ranPBTBDT, PBnDT-FTAZ, J71, PTzBi-Si, D18, D18-Cl, PDPPSDTPS, CC1C10-PPV, PBQX-TCI, P4T2F-HD, PCPDTBT, Si-PCPDTBT, PBT(TH), PBD(EDOT), PBD(TH), PDCBT, PDTPBT, PDCBT-CI, PTQ10, PNDI-5DD, PNDI-POD, IDTBT, PDMS, PS, and SEBS.

Citation Information

Patent Citations

  • Temperature-controllable device and method for testing creep performance of geomembrane in water environment

    CN108918289A

  • Electricity-force feedback carbon nanotube film orientation drafting strengthening device and method

    CN116840050A

  • Preparation method of self-supporting polymer film and variable-temperature stretching test method

    CN118500853A

  • In-situ variable-temperature stretching device for grazing incidence X-ray scattering characterization and testing method

    CN119000747A

  • Device for testing tensile property of organic film

    CN215065778U